Ludwig Senfl, Motets for Four Voices (A-I): New Senfl Edition 1 - Gasch, Stefan (2021)
The New Senfl Edition (NSE) begins with the publication of those works which have not yet been available in a modern edition: the motets for four voices. The first volume includes the innovative motet cycle Quinque Salutationes for the private devotion of Duke Wilhelm IV of Bavaria and the well-known Ecce quam bonum for the Imperial Diet in Augsburg 1530 in addition to many hitherto unknown motets. The Critical Reports accompanying the editions offer information on every motet with regard to the texts set to music, the plainchant models, an evaluation of the sources (incl. a synoptic overview of variant readings), as well as details on the history of each composition.